Limited knowledge flow among stakeholders of critically endangered renosterveld in South Africa - Stefanie Burghardt (Resilience Alliance, 2021)
Despite its status as a biodiversity hotspot, the renosterveld ecosystem within the Greater Cape Floristic Region, South Africa, widely lacks the implementation of measures for biodiversity conservation in the Swartland, even though management plans exist. Though formally protected by law, most renosterveld remnants occur on privately owned agricultural land and therefore depend on private land management. Effective measures, and therefore, effective management of renosterveld for conservation, require various forms of knowledge, including scientific and technical knowledge. Knowledge flows through networks among various stakeholders connected through social relationships and enables individuals to acquire, transmit, and create understanding. We assessed the flow of knowledge and advice through a social network of renosterveld stakeholders. We interviewed 53 individuals, of which 32 were renosterveld private land managers, to determine participants' knowledge sources and network connections. The resulting information and advice networks suggest that land managers are relatively isolated from renosterveld-related knowledge. Of the interviewed land managers, 19% did not identify any knowledge sources, and 91% stated they did not receive any advice. Members of academia provided most of the received knowledge (29%). Seventeen percent of all exchanged knowledge stemmed from governmental organizations, and 5% from land managers. The findings suggest that renosterveld land managers have limited access to biodiversity knowledge, and there are limited numbers of connections between land managers and external parties (e.g., researchers, conservationists). Thus, the current knowledge sharing structures are insufficient to inform conservation management of critically endangered renosterveld in the Swartland. In this context, bridging organizations and knowledge brokers are crucial components for biodiversity conservation.